Do parque infantil à EMEI: o que dizem as crianças sobre os espaços? - Russo, Adriana Siqueira (2020)
This research aimed to the physical spaces of Municipal School of Early Childhood Education (Emei) at São Paulo, whose the building had its origin on a Children Playground (PI) coined by Mário de Andrade. The study was motivated by the following questions: What are the Emei spaces used by the children? How and when do they used these spaces? What the activities are performed by the children in the different spaces? The main point was analyze what the children have to say about the research objective, recognizing its role. As specific objectives we outline: identify which spaces are used by the children; verify how and when do they use these spaces and identify the activities performed by the children in the different spaces. It was a qualitative nature research, and the data collection instruments was the observation about spaces used by the children and the conversation with the littles ones. Ten children participated of the study, aged between 5 and 6 years old, duly registered in the unit. The theoretical framework was based on following authors: Miguel Zabalza and Maria da Graça Souza Horn to support the space category; Mário de Andrade and Ana Lúcia Goulart de Faria to support the children playground category; Manuel Jacinto Sarmento to support the sociology of childhood category; Tizuko Morchida Kishimoto and Maria Carmen Silveira Barbosa to support the child education category. After our observation and conversation with the children was possible to list three categories, to know: environment, play and pedagogical intentionality. The results show that the utilization of the environments today is quite different of was proposed by the children playground, being currently defined by adults, to fulfill what is established in a fixed timeline, invariable and previously organized. As well as the complexity that involves the act of the observation and attentive listening of children, in the adultocentric routine of the Emei. However, through training and awareness, it is possible to look for inspiration in history and the legacy left by PIs of Mário de Andrade to reframing of practices and offer a quality public early childhood education.